Group photograph
Nine people pose on the front porch at 780 Irene Street. From left to right: Pat Romanello, Tony Talesfore, Roland Cantando, Gene Talesfore, Arnie Romanello, Luisa Massa Albanese, Rosie Albanese Romanello, and Marie Massa Albanese. Sitting: Marvie McArthur.